Evaluation of automated hematology analyser: Mindray BC-6800 plus as a screening tool for diagnosing malaria - Dhanani, Hiren J. (International Journal of Research in Medical Sciences, 2020)
Background: Malaria is one of the major health problems of developing and tropical countries like India, causing huge financial burden also. Smear examination for diagnosis is a routine and cost-effective method for diagnosis. CBC is one the most commonly ordered test in clinical practice. The Mindray BC-6800 plus haematology analyser provide dedicated flag of “Infected RBC?” for suspected malaria while analysing CBC. Present study attempts to evaluate whether CBC done on BC-6800 plus can serve as an aid for malaria screening and diagnosis. Methods: Prospective study of 30077 cases was carried out where thick and thin smear examination done by experienced microscopists and CBC was analysed on BC- 6800 plus analyser. Results: Total 323 cases were found to be positive for malaria by smear examination, out of which 285 were of P. vivax and 38 were of P. falciparum malaria. Sensitivity of 88.24%, specificity of 99.21%, PPV of 54.70%, NPV of 99.87% for Infected RBC flag for all cases of malaria. For P. vivax malaria cases analyser provided highest sensitivity of 99.65% with NPV of nearly 100%, however P. Falciparum malaria cases analyser produced sensitivity of 2.63% only. In P. vivax cases present study found very good correlation between InR count and parasite load under microscope. Present study also evaluated interference of parasitized red cells in differential count causing falsely elevated neutrophils and/or eosinophils. Conclusions: By lowering threshold for “Infected RBC?” flag to 0, BC-6800 plus can serve as an excellent screening tool especially for P. vivax malaria.